2021
DOI: 10.3389/fphar.2021.649472
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Pharmacological Interventions for Covid-19: A Systematic Review and Network Meta-Analysis

Abstract: Background: Several pharmacological interventions are now under investigation for the treatment of Covid-19, and the evidence is evolving rapidly. Our aim is to assess the comparative efficacy and safety of these drugs.Methods and Findings: We performed a systematic review and network meta-analysis searching Medline, Pubmed, Embase, Cochrane Covid-19 register, international trial registers, medRxiv, bioRxiv, and arXiv up to December 10, 2020. We included all randomised controlled trials (RCTs) comparing any ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…In addition, we mainly focused on the efficacy of interventions in this NMA and did not evaluate the corresponding safety profiles. Evidence from other NMAs ( 7 , 179 ) showed that most of investigated treatments in this NMA did not lead to increased adverse events, and remdesivir and lopinavir/ritonavir were associated with fewer occurrences of adverse events and serious adverse events, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, we mainly focused on the efficacy of interventions in this NMA and did not evaluate the corresponding safety profiles. Evidence from other NMAs ( 7 , 179 ) showed that most of investigated treatments in this NMA did not lead to increased adverse events, and remdesivir and lopinavir/ritonavir were associated with fewer occurrences of adverse events and serious adverse events, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…The data from our study close the gap between retrospective observations by presenting a potential mechanism of ASM release and action in COVID-19 patients. Keeping the paucity of proven host-directed therapies in mind, the low level of evidence of the majority of all running trials (14,99) and due to the fact that a panel of FDA-approved drugs with low risk of adverse effects is awaiting consequent investigation, the potential usefulness of antidepressants in patients with COVID-19 taking FIASMA for other indications with now known guiding principles should be prioritized for RCT and can minimize the risk of being exposed to novel, potentially harmful of ineffective compounds or compounds with unknown mode of action. As also recommended by others, the results support the continuation of FIASMA medication in these patients (69).…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplant recipients have higher mortality from coronavirus disease 2019 (COVID-19) compared with the general population. 1 , 2 In the absence of effective treatment, 3 the early use of convalescent plasma emerged as an alternative therapy with a favorable safety profile.…”
mentioning
confidence: 99%